Peer Review in the Artificial Intelligence Era: A Call for Developing Responsible Integration Guidelines - BaHammam AS (Nature and Science of Sleep)
Ahmed Salem BaHammam1– 3 1Editor-in-Chief Nature and Science of Sleep; 2Department of Medicine, University Sleep Disorders Center and Pulmonary Service, King Saud University, Riyadh, Saudi Arabia; 3King Saud University Medical City, Riyadh, Saudi ArabiaCorrespondence: Ahmed Salem BaHammam, University Sleep Disorders Center, Department of Medicine, College of Medicine, King Saud University, Box 225503, Riyadh, 11324, Saudi Arabia, Tel +966-11-467-9495, Fax +966-11-467-9179, Email ashammam2@gmail.com